Measures to prevent health care-related infections: integrative literature review (Research, Society and Development, 2022)
Health Care-Related Infections (HAI) are one of the main causes of mortality, being considered a serious public health problem. These infections bring several complications to the individual's health, increasing their hospitalization time, increasing care costs and favoring the spread of microorganisms. This study aims to demonstrate the measures to prevent infections related to health care. This is an integrative literature review, carried out in May and June 2022. The search strategies allowed the identification of 2390 articles in the Google Scholar database. During the analysis of titles and abstracts, applying the inclusion criteria, 2380 articles were excluded. In total, 10 were selected because they met all the requirements. There are several ways to prevent infections related to health care, among them are hand hygiene, the use of masks, gloves, glasses and among others, the contact precaution to prevent the spread of infectious agents transmitted by the colonized patient or infected by microorganisms, respiratory preventive measures which include precautions for droplets, sneezing and speaking, and finally, precautions for aerosols. Therefore, it is clear that the implementation and implementation of measures to prevent infections related to health care is imprescriptible, aiming to reduce the impacts on the lives of individuals.